The attributable mortality of sepsis for acute kidney injury: a propensity-matched analysis based on multicenter prospective cohort study. Issue 1 (31st December 2023) - Jia, Hui-Miao; Jiang, Yi-Jia; Zheng, Xi; Li, Wen; Wang, Mei-Ping; Xi, Xiu-Ming; Li, Wen-Xiong
Abstract: Background: Both sepsis and AKI are diseases of major concern in intensive care unit (ICU). This study aimed to evaluate the excess mortality attributable to sepsis for acute kidney injury (AKI). Methods: A propensity score-matched analysis on a multicenter prospective cohort study in 18 Chinese ICUs was performed. Propensity score was sequentially conducted to match AKI patients with and without sepsis on day 1, day 2, and day 3–5. The primary outcome was hospital death of AKI patients. Results: A total of 2008 AKI patients (40.9%) were eligible for the study. Of the 1010 AKI patients with sepsis, 619 (61.3%) were matched to 619 AKI patients in whom sepsis did not develop during the screening period of the study. The hospital mortality rate of matched AKI patients with sepsis was 205 of 619 (33.1%) compared with 150 of 619 (24.0%) for their matched AKI controls without sepsis ( p = 0.001). The attributable mortality of total sepsis for AKI patients was 9.1% (95% CI: 4.8–13.3%). Of the matched patients with sepsis, 328 (53.0%) diagnosed septic shock. The attributable mortality of septic shock for AKI was 16.2% (95% CI: 11.3–20.8%, p < 0.001). Further, the attributable mortality of sepsis for AKI was 1.4% (95% CI: 4.1–5.9%, p = 0.825). Conclusions: The attributable hospital mortality of total sepsis for AKI were 9.1%. Septic shock contributes to major excess mortality rate for AKI than sepsis. Registration for the multicenter prospective cohort study: registration number ChiCTR-ECH-13003934